Accreditation Handbook - Norazzlina, M.Sa'don; Lim, Soh Fong; Syed Tarmizi, Bin Syed Shazali; Sharifah Masniah, Wan Masra; Dygku Salma, Awg Ismail; Abdul Razak, Abdul Karim; Siti Nor Ain, Musa; Tan, Ivy Ai Wei; Wan Hashim, Wan Ibrahim; Al-Khalid, Hj Othman (UNIMAS Publisher, 2011)
This handbook is a reference for the faculty, academic and administrative staff on the process and procedures involved in preparing and obtaining accreditation. This handbook also serves as a valuable guide for the faculty to develop an assessment plan in the process of future accreditation.